The first use of bone tools: a reappraisal of the evidence from Olduvai Gorge, Tanzania - Backwell, Lucinda R.; d’Errico, Francesco (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2004)
Purported early hominid bone tools from Olduvai Gorge are studied for microscopic traces of use-wear, and evidence of intentional flaking by knapping. Comparative microscopic analyses of the edges of the purported tools, and areas far from the potential functional zone, as well as edges of bone pieces from the remainder of the assemblage, show that possible modifications due to utilization are not distinguishable from features attributed to post-depositional abrasion. Taphonomic analysis of the bone tool collection, a control sample of bone shaft fragments from the remainder of the Olduvai assemblage, and experimentally broken elephant long bones, identifies significant differences in the size and type of mammals represented. The bone tool collection records an abundance of large to very large mammals, while the control sample comprises mostly medium-size bovids. Puncture and cut-marks occur on one third of the bone tool collection, and on only a few pieces in the control sample, suggesting hominids were the agent responsible for the breakage of most of the bones previously described as tools. Analysis of the number, location and length of flake scars in the three assemblages, reveals that a reduced proportion of purported bone tools bear invasive, contiguous, often bifacially arranged removals, not seen in the control or experimental collections. This makes these specimens good candidates for having been shaped and used by early hominids. Complete bones with tool-generated puncture-marks, previously interpreted as anvils, are interpreted here as hammers used on intermediate stone tools.